Using Instagram as a Medium for Discussion in Paragraph Writing Course at Universitas Negeri Padang - Desi Amelia; Witri Oktavia (Universitas Negeri Padang, 2021)
The pandemic outbreak on 2019 impacts on students’ discussion activities in paragraph writing course of the 1st year English Student Department at Universitas Negeri Padang. In order to solve the problem, IT development provides social media, Instagram, as medium for the discussion through caption and comment feature. This paper explains on how to use Instagram as medium for paragraph writing discussion. The discussion is constructed through Instagram by dividing the activities into pre-teaching, whilst-teaching and post-teaching activities. The first activities is done by uploading the materials and students’ writing. After that, students and lecturer discuss about the material and students’ writing by giving sugesstion or feedback on the comment feature. On the final activities, through the feedback giving, students can improve their writing before collect it to the lecturer.